MicroRNA-99b predicts clinical outcome of osteosarcoma and suppresses tumor cell proliferation, migration and invasion - Xin Shi; Xingfa Guan (BMC, 2019)
Abstract Background Osteosarcoma (OS) is a malignancy predominantly occurred in children and adolescents. Numerous microRNAs are involved in the pathogenesis of various cancers. This study aimed to investigate the expression profiles of miR-99b and its prognostic value in OS patients, and further analyze the biological function of miR-99b in the tumor progression by using OS cells. Methods Expression of miR-99b was measured using quantitative real-time PCR. Kaplan-Meier survival curves and Cox regression analysis were performed to evaluate the prognostic value of miR-99b. OS cell lines were used to investigate the effects of miR-99b on cell proliferation, migration and invasion. Results A significant decreased expression of miR-99b was observed in the OS tissues and cell lines respectively compared with the normal tissues and cells. Aberrant expression of miR-99b was associated with the patients' metastasis and TNM stage, and could be used to predict the prognosis of OS. The expression of miR-99b was regulated in vitro by cell transfection, and we found that the overexpression of miR-99b led to suppressed cell proliferation, migration and invasion, whereas the knockdown of miR-99b resulted in the opposite results. Conclusions In one word, the aberrantly expressed miR-99b serves a prognostic biomarker for OS patients. OS cell proliferation, migration and invasion can be inhibited by the overexpression of miR-99b, suggesting that the methods to increase miR-99b expression may be novel therapeutic strategies in OS.